Methods and Applications in Respiratory Physiology: Respiratory Mechanics, Drive and Muscle Function in Neuromuscular and Chest Wall Disorders - Patel, Nina; Chong, Kelvin; Baydur, Ahmet (Frontiers in Physiology, 2022)
Neuromuscular and chest wall disorders result in respiratory muscle weakness, reduced lung volume and increases in respiratory elastance and resistance which lead to increase in work of breathing and eventually pump failure and impaired gas exchange. Recently developed methods to assess respiratory muscle weakness, mechanics and movement supplement traditionally employed spirometry and methods to evaluate gas exchange. These include recording postural change in vital capacity, respiratory pressures (mouth and sniff), electromyography and ultrasound evaluation of diaphragmatic thickness and excursions. In this review, we highlight key aspects of the pathophysiology of these conditions as they impact the patient and their quality of life and describe measures to evaluate respiratory dysfunction.